Kontinuitas, Perubahan, dan Fungsi Krinok pada Masyarakat Batin di Dusun Rantau Pandan, Kab. Bungo, Jambi - Rahmatika Luthfiana Sholikhah (Journal of Demography, Ethnography and Social Transformation, 2022)
Krinok is a song that was used as a means of communication and self-entertain. It is sung while working in the fields and at lek gedang, beselang gedang events or to welcome the king or regional head. Over time, the function and usability of Krinok changed. Culture is dynamic so change is inevitable. In the process of change, there are several factors that cause the culture to change, such as technology. This research is qualitative research and uses the ethnomusicology method by conducting literature study, observation, and interviews. In this study, changes in function that occur in Krinok are an effort to preserve culture.